Adsorptive Applications of Montmorillonite Clay for the Removal of Ag(I) and Cu(II) from Aqueous Medium. (23rd June 2019) - Alandis, Naser M.; Mekhamer, Waffa; Aldayel, Omar; Hefne, Jameel A. A.; Alam, Manawwer
Abstract : The present work aims to investigate the ability of Saudi clay containing montmorillonite to remove Ag(I) and Cu(II) ions from aqueous solutions for waste water purification. The effect of pH, adsorbent mass, metal concentration, and contact time on the removal process has been investigated. The batch method was applied, using solution metal concentrations ranging from 40 to 2000 mg/L. Adsorption percentage and distribution coefficients ( K d ) were determined as a function of metal concentration. pH 6 was found to be optimal for the adsorption. Adsorption reached equilibrium in 5 min for both Ag(I) and Cu(II) ions. The study on adsorption's kinetic characteristics showed the adsorption process of these metal ions was of pseudo-second-order. Furthermore, the adsorption rate of Ag(I) was higher than that of Cu(II), and their adsorption appeared to follow the Langmuir isotherm. From the equilibrium studies, it was observed that the selectivity of Ag(I) was higher than that of Cu(II). The results showed that Saudi clay has the potential to be a suitable adsorbent for Ag(I) and Cu(II) removal from aqueous solutions compared with other adsorbents.